Peran Azolla dalam Memperkaya Amelioran Organik sebagai Pupuk Hayati Padat dan Cair pada Padi Organik - Setiawati, Mieke Rochimi; Suswanto, Irwan; Suryatmana, Pujawati (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2025)
Improvement of rice productivity can be achieved by conducting farming efficiency and utilizing local resources. The Azolla water fern is a local resource that can be used as organic fertilizer in organic farming. Organic farming is a cultivation technique that utilizes organic materials to preserve the production environment so that the sustainability of agriculture can be maintained. This study aimed to determine the efficiency of the use of organic ameliorant added with Azolla sp. compost and biological fertilizers on soil C-organic content, C/N ratio of soil and organic rice yields. This research was conducted at the Experimental Station of the Faculty of Agriculture, Universitas Padjadjaran. The design used was randomized block design (RBD) with six treatments and four replications. The treatment is used in the form of a combination of organic ameliorants (straw and animal manure 10 tons ha-1 and straw, Azolla sp. and compost 7.5 tons ha-1) and solid and liquid biofertilizers with doses each of 10 kg ha-1 and 5 L ha-1. Result showed that the soil treated with combination of organic ameliorant added Azolla sp with solid biofertilizer had higher C-organic content compared to other treatments. Whereas the aplication of organic ameliorant added with Azolla sp. combined with liquid biofertilizers has increased organic rice yield.